Raising an Alternative Voice - Assessing the Role and Value of the Global Alternative News Agency Inter Press Service - Joye, Stijn (Javnost-The Public, 2009)
Inter Press Service (IPS) is widely considered to be distinctly diff erent from the conventional news agency. Research on this alternative news agency has mainly focused on the IPS news to underwrite this statement, but much less attention has been paid to the broader production context. Drawing on the findings of twenty-six semi-structured in-depth interviews, this article explores the value and role of IPS in the digital news market of the 21st century as perceived by staff members, stakeholders and independent scholars. In general, interviewees argue that IPS and its news copy are a useful and necessary addition to mainstream news media, as well as a crucial source of information and a partner for the global civil society. However, the study also indicates that IPS will need to face a number of professional, organisational and financial challenges if the news agency aspires to continue its unique role of sensitising the public and bridging the information gap between North and South.